2018
DOI: 10.1177/1479164118804451
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin and insulin-like growth factor binding protein-1 during follow-up after an acute myocardial infarction in patients with type 2 diabetes: A report from the Diabetes Mellitus Insulin-Glucose Infusion in Acute Myocardial Infarction 2 cohort

Abstract: Copeptin and insulin-like growth factor binding protein-1 analysed at admission for a myocardial infarction in patients with type 2 diabetes mellitus predicts cardiovascular events. The present aim was to study the association between copeptin and insulin-like growth factor binding protein-1, the development of the levels over time, and if the predictive value remained when measured at hospital discharge and 3 months thereafter. Methods: Copeptin and insulin-like growth factor binding protein-1 were analysed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In a DIGAMI substudy, copeptin levels were measured at admission ( n = 393), on discharge ( n = 309), and 3 months after MI ( n = 288) in patients with type 2 diabetes mellitus [ 70 ]. Copeptin at different time points was associated with outcomes, but the most consistent association was for admission copeptin, which maintained its predictive value in adjusted models for CV events, for CV death, and for combined non-fatal MI or stroke [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a DIGAMI substudy, copeptin levels were measured at admission ( n = 393), on discharge ( n = 309), and 3 months after MI ( n = 288) in patients with type 2 diabetes mellitus [ 70 ]. Copeptin at different time points was associated with outcomes, but the most consistent association was for admission copeptin, which maintained its predictive value in adjusted models for CV events, for CV death, and for combined non-fatal MI or stroke [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compelling data indicated copeptin as an excellent predictor of outcomes of patients with heart failure and acute myocardial infarction (AMI); its accuracy was even superior to that of NT-proBNP 27,28 . Others also indicated that copeptin possessed the potential to be a surrogate marker for acute lung injury, glucose abnormalities with AMI, birth asphyxia, multiple organ dysfunction, death in the intensive care units, cardiac stress after generalized convulsive seizures, and neurological dysfunction and mortality in post-CA syndrome [29][30][31][32][33] . Moreover, CT-proAVP was reported to be associated with hypopituitarism 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Smaradottir et al analysed copeptin levels in patients with type 2 diabetes and myocardial infarction at admission, discharge and three months later and discovered that copeptin serum concentrations at admission were significantly higher than at subsequent time points. Moreover, copeptin turned out to be a significant predictor for cardiovascular events at all time points [47].…”
Section: Copeptin and Diabetic Macroangiopathymentioning
confidence: 92%